1999
DOI: 10.1053/joca.1998.0216
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide in osteoarthritis

Abstract: Activated articular chondrocytes produce large amounts of nitric oxide (NO), and there is increasing evidence that this is involved in the etiopathogenesis of osteoarthritis (OA). Because of its short half-life, the biological effects of endogenously produced NO are likely to occur locally within the cartilage. We have observed that inhibitors of NO synthases relieve the inhibition of matrix synthesis that otherwise occurs in response to IL-1. To avoid the use of inhibitors, we have recently transduced chondro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
125
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(131 citation statements)
references
References 17 publications
6
125
0
Order By: Relevance
“…However, numerous studies have shown that OPG levels will rise in a coordinated manner when RANKL levels are increasing. This is consistent with the observation of elevated OPG in synovial fluid from RA patients but not from OA patients (36). In relation to this finding, we observed an opposite effect of TNF␣ on OPG expression in repair chondrocytes isolated from fracture calluses, suggesting that while some actions of TNF␣ appear to be the same for all chondrocytes, other activities may vary between growth and articular chondrocytes.…”
Section: Discussionsupporting
confidence: 92%
“…However, numerous studies have shown that OPG levels will rise in a coordinated manner when RANKL levels are increasing. This is consistent with the observation of elevated OPG in synovial fluid from RA patients but not from OA patients (36). In relation to this finding, we observed an opposite effect of TNF␣ on OPG expression in repair chondrocytes isolated from fracture calluses, suggesting that while some actions of TNF␣ appear to be the same for all chondrocytes, other activities may vary between growth and articular chondrocytes.…”
Section: Discussionsupporting
confidence: 92%
“…43 We observed that the NO donor Noc-12 (2.5 to 25 mol/L), and the peroxynitrite generator Sin-1 (1 to 10 mol/L) 44 shared the ability of IL-1 to induce TGase activity in cultured normal knee meniscal cells, although Noc-12 and Sin-1 were less effective than IL-1 at inducing TGase activity (Figure 7). Tumor necrosis factor (TNF)-␣, which also acts on chondrocytes, 45,46 stimulated increased TGase activity in cultured normal knee meniscal cells (Figure 7).…”
Section: Mechanism Of Induction Of Tgase Activity By Il-1mentioning
confidence: 85%
“…Finally, IL-1 and TNF-α increase nitric oxide synthase leading to an increase of NO [60]. NO radicals have deleterious effect in joint cartilage including downregulation of matrix synthesis and upregulation matrix degradation via activation of MMPs [61][62][63]. Furthermore, NO increases chondrocyte susceptibility to oxidants while free radicals produced by NO were also shown to induce chondrocyte apoptosis [44,64,65].…”
Section: Cytokines Oxidative Damage and Chemokinesmentioning
confidence: 99%